BoNT/A alleviates neuropathic pain in osteoarthritis by down-regulating the expression of P2X4R in spinal microglia. (30th January 2022) - Yang, Hui; Wang, Lin; Chu, Xiao; Shi, Xiaojuan; Li, Xinhe; Li, Tieshan
Abstract: Neuropathic pain in osteoarthritis is one of the reasons why the pain is difficult to treat, and P2X4R plays an important role in neuropathic pain. In addition, BoNT/A has been proven to have analgesic effects on both neuropathic pain and osteoarthritis, but its exact mechanism is still unknown. This study aims to investigate the relationship between the analgesic effect of BoNT/A on osteoarthritis and the expression of P2X4R in spinal cord microglia. The analgesic effect was compared between BoNT/A and compound betamethasone. Western blot analysis was used to examine the expression of P2X4R and BDNF proteins in the spinal cord. Immunohistochemistry was used to determine the cellular location of P2X4R. Mechanical allodynia and weight asymmetry were identified using the hind paw withdrawal threshold and weight bearing test. The results showed that intra-articular injection of MIA induced persistent mechanical allodynia and weight asymmetry in rats. Both BoNT/A and betamethasone could relieve pain behavior in rats, but BoNT/A had a more obvious effect and lasted longer. Furthermore, BoNT/A could reverse the MIA-induced overexpression of BDNF and P2X4R in the spinal dorsal horn. To sum up, BoNT/A is more effective than betamethasone in relieving MIA-induced osteoarthritis pain in rats, and its analgesic effect may be related to the regulation of P2X4R-mediated BDNF release in spinal microglia and the relief of neuropathic pain in osteoarthritis. Highlights: Osteoarthritis involves both nociceptive pain and neuropathic pain. P2X4R mediated brain-derived neurotrophic factor release in spinal microglia plays an important role in neuropathic pain. BoNT/A can reverse sodium monoiodoacetate induced overexpression of P2X4R in the spinal dorsal horn. BoNT/A is more effective than betamethasone in relieving sodium monoiodoacetate induced osteoarthritis pain in rats. It is important to consider the type of pain in osteoarthritis before treatment.